SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEGAWAI PENERIMA REWARD MENGGUNAKAN PENDEKATAN TOPSIS - Sudaryono Sudaryono; Rochmawati Rochmawati (Jurnal Sistem Informasi dan Informatika (Simika), 2020)
The provision of employee reward for the best performance and achievement of duty is required to do by the organization/institution as the form of recognition and appreciation for the employees and as part of the organizational goal achievement process. This research aimed to develop a decision support system (SPK)) using TOPSIS method with PHP programming language and MySQL database to choose employees receiving rewards in Universitas Serang Raya. The data used derived from 2 groups namely educational employees consisting of lecturers and non-educational ones consisting of official employees. The criteria applied in the educational employees are 10 that are length of employment, dp3 value, percentage value of work attendance, percentage value of the lecturing attendance, value of the lecturer’s functional position, value of research deeds , value of community devotion , value of the questionnaire result by students, value of employment status, and value of sanctions. The criteria applied in the non educational employees are 5 that are length of employment, dp3 value, percentage value of work attendance, value of employment status, and value of sanctions. The result of this research is an information system program as a support decision tool for choosing employees receiving rewards